Steels microstructure and properties : - Bhadeshia, H. K. D. H. 1953-; Honeycombe, R. W. K. (Butterworth-Heinemann, 2017)
This volume outlines the principles determining the microstructure, mechanical behavior and properties of steels, the most widely-used metallic alloy. It is updated with new material on nanostructured steels, novel alloys for energy industries, and the latest technologies for the automobile industry.
Keywords: metalurgie; ocel; fyzikální metalurgie; metalografie; metallurgy; steel; physical metallurgy; metallography; monografie; monographs